The beginning of veterinary surgery education in Türkiye and the historical development of this discipline in Ankara University Faculty of Veterinary Medicine - Yerlikaya, Nigar; Küçükaslan, Özgül (Veteriner Fakültesi dergisi, 2024)
Research on the history of the fields of science has special meanings and importance in the history of veterinary medicine. Various studies are carried out on this subject, both at the level of scientific articles and at the level of large-scale doctorate. In this article, the beginning of the veterinary surgery field in Türkiye and its historical development in Ankara University Faculty of Veterinary Medicine, which is the oldest faculty, are discussed. The main material of the study was the first-hand archival resources provided by the Rectorate, Dean's Office and Departments of Ankara University. Various books and journals related to the subject were also used. The data obtained were evaluated within the framework of the historical methodology and were written down chronologically. The processes of the modern surgery education, which started with the Prussian Veterinarian Godlewsky in the Ottoman period, continued within the Higher Agricultural Institute and later Ankara University in the post-Republican period, the changes in the structure of the department with the changes in the university laws, the educational status, the academic stages and the number of publications until April 2022 of faculty members have been determined. The data obtained can shed light on the evaluations to be made in this field. As a result, it has been tried to present a well-coordinated source on the history of the field. The inclusion of detailed data on the surgical units of all veterinary faculties in Türkiye would enable the holistic determination of the quality of surgery in veterinary medicine.